The problems of the tourist industry in Kundasang, Sabah: The structuralist Marxist explanation - Ramzah Dambul,; Amriah Buang, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2008)
This paper is an exercise in a structuralist Marxist explanation of the two main problems underlining the relative failure of the Kundasang tourist industry in functioning as a catalyst for the development of the local area and to which the positivit perspective has not been able to offer a satisfactory explanation, namely: (a) why did the investment that flowed into Kundasang fail to generate the economic multiplier and spread effects at the local level?; and (b) why did the significant presence of migrant foreign workers not contribute to the growth of the retail and urban services segments in Kundasang ? The paper concludes that the two key problems were caused by the very nature of the capitalist mode of accumulation which thrived on unequal and opportunistic relations in order to extract the maximum returns for the capitalists involved in the Kundasang tourist industry. This is the real albeit non-empirical mechanism of ‘exploitation’ which the positivist epistemology has missed to acknowledge